2016
DOI: 10.1007/s40520-016-0675-6
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic hepatectomy for HCC in elderly patients: risks and feasibility

Abstract: LLR is safe and feasible as OLR for treatment of HCC in selected elderly patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 27 publications
1
41
0
Order By: Relevance
“…The characteristics of a total of 5100 patients from 43 studies included in the meta-analysis are specified in Table 1 [ 27 69 ]. The only randomized controlled trial was conducted by Jiang et al [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of a total of 5100 patients from 43 studies included in the meta-analysis are specified in Table 1 [ 27 69 ]. The only randomized controlled trial was conducted by Jiang et al [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…[ 19 , 22 – 24 , 26 ] Five studies used 70 years as the age cutoff the elderly label, [ 18 , 19 , 22 , 23 , 26 ] whereas 1 study used 65 years [ 24 ] and the other 3 studies used 75. [ 20 , 21 , 25 ] The indications of 2 studies included benign liver lesions and malignancy. [ 20 , 21 ] The indications of the remaining 7 studies were reported as malignant, with colorectal metastases the most frequently recorded.…”
Section: Resultsmentioning
confidence: 99%
“…One study was only restricted to primary hepatocellular carcinoma. [ 25 ] The majority type of intervention was total or pure laparoscopic hepatic resection, but 1 study used hand-assisted or hybrid procedures. [ 20 ] All of the included studies graded morbidity according to the Clavien-Dindo Classification.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations